Digitization of the manufacturing sector across the EU: assessing readiness for industry 4.0 - Branco, Maria Isabel Cabral de Abreu Castelo (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Information Systems and Technologies Management